Qualidade das internações hospitalares nos setores público e privado: um estudo comparativo a partir da opinião dos usuários nos estados do Maranhão, Piauí e Ceará - Lima, Valderi Lopes de (2009)
This study aims to examine the user satisfaction of hospital admissions in the States of Piauí, Ceará and Maranhão, according to the PNAD data for 1998 and 2003 in the face of relevant explanatory variables such as types of network , whether public or private network interaction with the year in question, coverage of health insurance, presence of chronic disease, place of residence (urban or rural), family income, race, and others, with the main focus of differential assessment quality of admissions in public and private sectors. Of the various econometric methods available: linear, logit, probit, etc.. We chose this work, the probabilistic logit econometric model, with, role-based logistic cumulative probability, where the dichotomous dependent variable equals 1 if the User's hospital assessed as satisfactory service, and zero otherwise, and the key explanatory variable is a dummy contrast between the public and private sectors. In the end, obtain parameters that will give a sensitive dimension of quality for the variables studied. Wanted to bring it to public managers and stakeholders in general a diagnosis that can be reflected in public policies that will reduce possible discrepancies found.